A method to obtain precise determinations of relative humidity using thin film capacitive sensors under normal or extreme humidity conditions. - Dario, Camuffo (Journal of Cultural Heritage, 2019)
• Taking precise relative humidity measurements even under extreme humidity conditions. • Improving performance of thin film capacitive sensors. • Using warmed-up sensors to precisely measure the dew point. • Relative humidity records made through temperature and dew point determinations. Dampness is one of the worst, and most common problems found in heritage buildings and sites. However, despite its relevance, sensors do not operate satisfactorily in extremely humid environments. The paper analyses the performance of heated capacitive sensors conceived to operate at ambient temperature (T) and very high relative humidity (RH) after having been demisted with short heating. Even if they show better performances than traditional, unheated sensors, they operate at the limit of their range, with severe limitations affecting their time response and accuracy, reducing but not excluding false readings. A method is proposed to combine temperature and relative humidity sensors, and warm-up them in order to reach the best performance interval of the RH sensor, and take measurements in such conditions, i.e. at higher temperature and lower relative humidity. From the combined temperature and relative humidity readings it is possible to calculate the dew point that is invariant to temperature changes. Combining the dew point with an additional measurement of the actual air temperature, it is possible to calculate the actual relative humidity. The use of this method is not necessarily limited to taking more accurate relative humidity readings under extreme dampness, but it may be also applied to improve the quality of readings with sensors that operate in their best performance interval. The same strategy can be used in too dry environments with cooling to raise relative humidity and bring the sensor into the best performance interval.